2021
DOI: 10.1021/acsami.1c00502
|View full text |Cite
|
Sign up to set email alerts
|

Monolithic Metal–Semiconductor–Metal Heterostructures Enabling Next-Generation Germanium Nanodevices

Abstract: Low-dimensional Ge is perceived as a promising building block for emerging optoelectronic devices. Here, we present a wafer-scale platform technology enabling monolithic Al-Ge-Al nanostructures fabricated by a thermally induced Al-Ge exchange reaction. Transmission electron microscopy confirmed the purity and crystallinity of the formed Al segments with an abrupt interface to the remaining Ge segment. In good agreement with the theoretical value of bulk Al-Ge Schottky junctions, a barrier height of 200 ± 20 me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…Both the STEM and HRTEM images reveal a sharp interface with finite (atomic level) roughness at the Al-Ge junction that is inclined with respect to the viewing direction and does not show any indications of chemical intermixing. Based on extensive TEM investigations on the Al-Ge exchange for vapor-liquid-solid grown Ge nanowires and top-down fabricated Ge nanosheets, [21] it was shown that the Al propagation is governed by Ge diffusion via surface channels on the Al to the extended contact pads. The Al replacing the Ge is thereby provided by effective Al self-diffusion.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Both the STEM and HRTEM images reveal a sharp interface with finite (atomic level) roughness at the Al-Ge junction that is inclined with respect to the viewing direction and does not show any indications of chemical intermixing. Based on extensive TEM investigations on the Al-Ge exchange for vapor-liquid-solid grown Ge nanowires and top-down fabricated Ge nanosheets, [21] it was shown that the Al propagation is governed by Ge diffusion via surface channels on the Al to the extended contact pads. The Al replacing the Ge is thereby provided by effective Al self-diffusion.…”
Section: Resultsmentioning
confidence: 99%
“…Thus Al contamination in Ge is unlikely. [21] Figure 1d,e shows representative TEM images of a monolithic Al-Ge-Al heterostructure, with the interface being composed of a Ge {111} and an Al {200} facet, respectively. While both crystals are oriented in a [110] zone axis, a mutual in-plane rotation of 6.5° was measured, which might be associated to strain compensation and lattice relaxation to accommodate the lattice mismatch between Ge and Al.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations